Investigating Factors Leading to Develop Academic Dishonesty and Cheating Behaviors During Board Examinations in Balochistan, Pakistan - Ali, Wazir; Aftab, Arjamand; Nur, Andi Cudai; Ibrahim, Aya Ragab; Mohamed, Ahmed Abdi (Faculty of Humanities, Universitas Jenderal Soedirman, 2024)
This study investigates the pervasive issue of academic dishonesty and cheating behaviors during board examinations in Balochistan, highlighting diverse contributing factors and underscoring the pivotal role of exams in shaping academic paths. The study adopted a quantitative approach, 200 student responses collected through nonprobability random sampling. Using the rational choice theory, this study fills a research gap and advances understanding of academic dishonesty by offering insightful information. Empirical data analysis was utilized to conclude. The research reveals a high incidence of cheating from students with various causes, including the fear of failure, societal expectations, and peer pressure associated with examinations. Notably, stress and anxiety emerge as key predictors of academic dishonesty. Students, facing intense academic pressures, often turn to unethical practices as a coping mechanism. The study underscores the inadvertent encouragement of cheating within the education system, driven by an excessive focus on exam results as the primary measure of success. The findings contribute valuable insights to the academic integrity discourse, advocating for comprehensive strategies to foster a healthier educational system in Balochistan. Recommendations include addressing root causes, promoting a supportive learning environment, fostering open dialogue, and promoting a broader definition of success. formative assessments, post-exam feedback, parental collaboration, and workshops on academic integrity are proposed to create a more supportive and ethical learning environment, enforcing academic honor codes, strict exam monitoring, and efforts to mitigate cheating should extend beyond punitive measures and implement initiatives to reshape perceptions of success, ultimately cultivating a culture of honesty and integrity in education.